If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4 + -1i) + -1(6 + -3i) = 0 Remove parenthesis around (4 + -1i) 4 + -1i + -1(6 + -3i) = 0 4 + -1i + (6 * -1 + -3i * -1) = 0 4 + -1i + (-6 + 3i) = 0 Reorder the terms: 4 + -6 + -1i + 3i = 0 Combine like terms: 4 + -6 = -2 -2 + -1i + 3i = 0 Combine like terms: -1i + 3i = 2i -2 + 2i = 0 Solving -2 + 2i = 0 Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 2i = 0 + 2 Combine like terms: -2 + 2 = 0 0 + 2i = 0 + 2 2i = 0 + 2 Combine like terms: 0 + 2 = 2 2i = 2 Divide each side by '2'. i = 1 Simplifying i = 1
| 6d+22d+12=0 | | 3056890000-15000000x=2085000000+55000000x | | .50n=17 | | 10x+6=6x+7 | | 4x-10=5x-20 | | 16y+11y^2=12 | | 4(x+2)-3=2x+1 | | 5-3(4-2b)=4(b-3) | | 19-20b=18 | | 3x-(x+1)=41 | | 16n=5n | | 5x-12=4-6x | | -2(-3x)=8x+2x | | -37=3-8x | | 19x=49-10 | | 6x-4-3x=20 | | (3a+7)(2a-5)= | | 4x^2+47x+70=0 | | 10(x+.50)=3x+5+7x | | (-19)*y=1900 | | 36x=8x | | 4x+8x=12-10 | | x^3-5x^2+12=0 | | 5+-11n=24 | | (12)(-5)n=0 | | 42=-29(y+5) | | -7(y+4)-6y= | | X^2-7x=-144 | | 2x+x+4+2=3(x+2) | | 49=7f | | b+5=-2b-3 | | 7+2(x-6)=-3+2x(x-1) |